Влияние модификации поверхности скаффолдов никелида титана кукурбит[6]урилом на гемолитический эффект - Федоришин, Дмитрий Александрович (Перспективы развития фундаментальных наук. Т. 4 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Currently, materials based on titanium nickelide with shape memory effects (SME) and superelasticity (SE) are developed. However, their biocompatibility is not always sufficient for use in medicine. One way to improve biocompatibility is to modify these materials with nitrogen-containing supramolecular heterocycles. In this study, the cytocompatibility of titanium nickelide scaffolds modified by CB[6] studied by assessing their hemolytic activity. The low hemolytic activity of modified CB[6] samples was shown. The optimal parameters for assessing the hemocompatibility of such samples were established.